Clinical safety and activity of pembrolizumab in patients with malignant pleural mesothelioma (KEYNOTE-028): preliminary results from a non-randomised, open-label, phase 1b trial. Issue 5 (May 2017) - Alley, Evan W; Lopez, Juanita; Santoro, Armando; Morosky, Anne; Saraf, Sanatan; Piperdi, Bilal; van Brummelen, Emilie
Summary: Background: Malignant pleural mesothelioma is a highly aggressive cancer with poor prognosis and few treatment options following progression on platinum-containing chemotherapy. We assessed the safety and efficacy of pembrolizumab (an anti-programmed cell death receptor 1 [PD-1] antibody) in advanced solid tumours expressing programmed cell death ligand 1 (PD-L1) and report here on the interim analysis of the malignant pleural mesothelioma cohort. Methods: Previously treated patients with PD-L1-positive malignant pleural mesothelioma were enrolled from 13 centres in six countries. Patients received pembrolizumab (10 mg/kg every 2 weeks) for up to 2 years or until confirmed progression or unacceptable toxicity. Key eligibility criteria included measurable disease, failure of standard therapy, and Eastern Cooperative Oncology Group performance status of 0 or 1. PD-L1 positivity was defined as expression in 1% or more of tumour cells by immunohistochemistry. Response was assessed based on investigator review using the Response Evaluation Criteria in Solid Tumors (RECIST; version 1.1). Primary endpoints were safety and tolerability, analysed in the all-patients-as-treated population, and objective response, analysed for the full-analysis set. This trial is registered withClinicalTrials.gov, numberNCT02054806, and is ongoing but not recruiting participants. Findings: As of June 20, 2016, 25 patients received pembrolizumab. 16 (64%) patients reported a treatment-related adverse event; the most common adverse event were fatigue (six [24%]), nausea (six [24%]), and arthralgia (five [20%]). Five (20%) patients reported grade 3 treatment-related adverse events. Three (12%) patients required dose interruption because of immune-related adverse events: one (4%) of 25 each had grade 3 rhabdomyolysis and grade 2 hypothyroidism; grade 3 iridocyclitis, grade 1 erythema multiforme, and grade 3 erythema; and grade 2 infusion-related reaction. No treatment-related deaths or discontinuations occurred. Five (20%) patients had a partial response, for an objective response of 20% (95% CI 6·8–40·7), and 13 (52%) of 25 had stable disease. Responses were durable (median response duration 12·0 months [95% CI 3·7 to not reached]); two patients remained on treatment at data cutoff. Interpretation: Pembrolizumab appears to be well tolerated and might confer anti-tumour activity in patients with PD-L1-positive malignant pleural mesothelioma. Response durability and efficacy in this patient population warrants further investigation. Funding: Merck.